2016
DOI: 10.1016/j.nima.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Testbeam studies of pre-prototype silicon strip sensors for the LHCb UT upgrade project

Abstract: The LHCb experiment is preparing for a major upgrade in 2018-2019. One of the key components in the upgrade is a new silicon tracker situated upstream of the analysis magnet of the experiment. The Upstream Tracker (UT) will consist of four planes of silicon strip detectors, with each plane covering an area of about 2 m 2 . An important consideration of these detectors is their performance after they have been exposed to a large radiation dose. In this article we present test beam results of pre-prototype n-in-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…However, some of it is likely due to changes in the temporal and spacial charge collection properties in irradiated sensors. This effect has been seen in previous UT test beam studies [5]. middle between two strips (zero in the plot), the efficiency drops to about 88%.…”
Section: Results For the The Type B Sensorsupporting
confidence: 80%
See 2 more Smart Citations
“…However, some of it is likely due to changes in the temporal and spacial charge collection properties in irradiated sensors. This effect has been seen in previous UT test beam studies [5]. middle between two strips (zero in the plot), the efficiency drops to about 88%.…”
Section: Results For the The Type B Sensorsupporting
confidence: 80%
“…Those studies are documented in Refs. [5,6]. In this most recent beam test described here, two sensors were tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3b. An extensive test beam campaign has demonstrated that these features perform well, even after irradiation to the maximum fluences expected [4,5,6,7].…”
Section: Ut Componentsmentioning
confidence: 99%
“…The irradiated mini-sensors were wirebonded to Beetle chips that were designed for the current silicon strip detectors [12], and read out with an Alibava DAQ system [13,14]. The sensors were tested in an 180 GeV proton beam at CERN [15]. A TimePix3-based telescope was used to provide tracking precision of ∼2 µm on the detector under test [16].…”
Section: Silicon Sensor Randdmentioning
confidence: 99%